1998
DOI: 10.1037/1040-3590.10.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Addiction Severity Index (ASI) interviewer severity ratings for a computer-administered ASI.

Abstract: including a number of states, counties, and cities for This project was supported, in part, by Grant R43-DA09938-01 from programs they fund. The ASI is used worldwide and has been The Small Business Innovative Research (SBIR) program. Some of the tfaaa]Med into 13 languages. It has been expanded to specialdata analyzed were made available by the National Institute on Drug . , , . =«= r t Abuse Collaborative Cocaine Treatment Study, Grant U01 DA-O7663 lzed P°P ul <*«>ns such as cocaine-abusing mothers, cocaine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…The ASI–MV is self-administered, requires no training and minimal staff time, and eliminates interviewer variability. The ASI-MV has excellent test-retest reliability, good criterion validity, and convergent-discriminant validity that is equal to or stronger than the original convergent-discriminant validity evidence for the ASI (Butler et al, 1998; McLellan et al, 1980). …”
mentioning
confidence: 89%
“…The ASI–MV is self-administered, requires no training and minimal staff time, and eliminates interviewer variability. The ASI-MV has excellent test-retest reliability, good criterion validity, and convergent-discriminant validity that is equal to or stronger than the original convergent-discriminant validity evidence for the ASI (Butler et al, 1998; McLellan et al, 1980). …”
mentioning
confidence: 89%
“…The Addiction Severity Index has been the mainstay for drug treatment intake assessments since 1980, going through numerous revisions (McLellan et al, 1992), checks for internal consistency and validity (Leonhard, Mulvey, Gastfriend, & Shwartz, 2000), efforts to establish clinical norms (Weisner, McLellan, & Hunkeler, 2000), conversions to computer-assisted applications (Butler et al, 1998(Butler et al, , 2001, dissemination within new technologies (Carise, Cornely, & Gurel, 2002), and comparisons with alternative assessments (Joe, Simpson, Greener, & Rowan-Szal, in press). Continuing growth in technology makes Internet-based or on-line assessments a high priority for development and information management (Buchanan, 2002), but more work and resources clearly are needed.…”
Section: Defining Practical Patient Performance and Treatment Processmentioning
confidence: 99%
“…In fact, they found that all but one state studied required a master's degree for mental health counselor credentials, whereas the majority of states required a bachelor's degree or lower for substance abuse counselor credentials (Kerwin et al, 2006). It is likely that, with additional training, counselors could be taught to use the severity ratings more accurately Butler et al, 1998).…”
Section: Discussionmentioning
confidence: 96%